2013
DOI: 10.1002/adfm.201202476
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Organic Solar Cells by Using Shape‐Dependent Broadband Plasmonic Absorption in Metallic Nanoparticles

Abstract: It is been widely reported that plasmonic effects in metallic nanomaterials can enhance light trapping in organix solar cells (OSCs). However, typical nanoparticles (NP) of high quality (i.e., mono‐dispersive) only possess a single resonant absorption peak, which inevitably limits the power conversion efficiency (PCE) enhancement to a narrow spectral range. Broadband plasmonic absorption is obviously highly desirable. In this paper, a combination of Ag nanomaterials of different shapes, including nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
238
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(239 citation statements)
references
References 46 publications
1
238
0
Order By: Relevance
“…Plasmonic nanostructures, such as periodic metal gratings [88][89][90], metal NPs [91][92][93][94], random corrugations [95][96][97] and biomimetic structures [98][99][100], have been investigated universally involving light concentration and manipulation in OPVs. Various kinds of plasmonic nanostructures can effectively trap light inside the photoactive layer owing to the excitation of the surface plasmonic effect, which is the collective oscillations of conductive electrons at the metal/dielectric interface.…”
Section: Plasmonic Effect Enhances Light Trappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmonic nanostructures, such as periodic metal gratings [88][89][90], metal NPs [91][92][93][94], random corrugations [95][96][97] and biomimetic structures [98][99][100], have been investigated universally involving light concentration and manipulation in OPVs. Various kinds of plasmonic nanostructures can effectively trap light inside the photoactive layer owing to the excitation of the surface plasmonic effect, which is the collective oscillations of conductive electrons at the metal/dielectric interface.…”
Section: Plasmonic Effect Enhances Light Trappingmentioning
confidence: 99%
“…Choy et al [92] demonstrated broadband light trapping in OPVs with multi-plasmonic-resonant absorption peaks based on metal NPs. They incorporated Ag NPs and nanoprisms with different shapes synthesized by a wet chemical method in P3HT:PCBM photoactive layers as shown in Figure 8D and E, and low-order and high-order plasmonic resonance modes were excited simultaneously in broadband.…”
Section: Lsprmentioning
confidence: 99%
“…Inorganic nanocrystals (INCs) can also be included into BHJ film, which is an extensively adopted strategy to enhance device performances [65][66][67][68][69]. The main focus lies on their unique plasma effects for enhancing light scattering path within the thin films.…”
Section: Inorganic Nanocrystalsmentioning
confidence: 99%
“…Therefore, there was an amount of attempts to enhance light emitting diodes (LED) based on particular wavelength [4,5]. However, the enhancement of light is the issue not only for the LED, but also for the many kinds of photonic devices including solar cells [6][7][8].…”
Section: Introductionmentioning
confidence: 99%